Challenges to drug discovery for celiac disease and approaches to overcome them. (3rd October 2019) - Vaquero, Luis; Bernardo, David; León, Francisco; Rodríguez-Martín, Laura; Alvarez-Cuenllas, Begoña; Vivas, Santiago
ABSTRACT: Introduction : The only available effective treatment for celiac disease (CD) is strict and long-term compliance with a gluten-free diet. Dietary gluten restriction must be strict and long term, but is difficult to achieve in many cases and alternative dietary strategies have been investigated in the past few years. Areas covered : This review highlights the progress that has been made in the development of new therapeutics for CD. Detailed information is provided on the targets of drugs for CD as their related mechanisms of action. The therapies are classified in five mechanisms: modification of gluten, intraluminal therapies, immunomodulation, intestinal permeability and modulation of adaptative response. The actual development phase and future approach are also described and discussed. Expert opinion : There are several limitations in each of the treatment targets related either through complications or the lack of complete response to a normal gluten containing diet. It is clear that the most desired therapy for celiac patients would induce gluten tolerance and progress has been made as per the treatments described herein. Therefore, it is shortly expected that curative or complimentary tools to a gluten free diet will be available that will improve the quality of life of CD sufferers.